2022
DOI: 10.18632/aging.204075
|View full text |Cite
|
Sign up to set email alerts
|

A novel lncRNA-miRNA-mRNA triple network identifies lncRNA XIST as a biomarker for acute myocardial infarction

Abstract: Despite the well-established role of long non-coding RNAs (lncRNAs) across various biological processes, their mechanisms in acute myocardial infarction (AMI) are not fully elucidated. The GSE34198 dataset from the Gene Expression Omnibus (GEO) database, which comprised 49 specimens from individuals with AMI and 47 specimens from controls, was extracted and analysed using the weighted gene co-expression network analysis (WGCNA) package. Twenty-seven key genes were identified through a combination of the degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…The chi-square test was used to analyse measurement data, such as the number of drinkers and smokers, and the sex ratio. Based on previous studies [21], MedCalc software (MedCalc Software, Mariakerke, Belgium, version 19.7.4) was used to perform nonparametric receiver operating characteristic (ROC) curve analysis. R software (version 4.1.0) was used to perform the bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chi-square test was used to analyse measurement data, such as the number of drinkers and smokers, and the sex ratio. Based on previous studies [21], MedCalc software (MedCalc Software, Mariakerke, Belgium, version 19.7.4) was used to perform nonparametric receiver operating characteristic (ROC) curve analysis. R software (version 4.1.0) was used to perform the bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The genes with the top 25% of variance were selected for the WGCNA analysis. In this study, the appropriate soft threshold was defined as 18, and the WGCNA analysis was carried out according to methods detailed in our latest publication [21].…”
Section: Wgcna Analysis Identified Modules That Were Significantly As...mentioning
confidence: 99%
“…Genes with the top 25% of variance were selected for the WGCNA. In the current research, the appropriate soft threshold was defined as 14, and detailed WGCNA steps refer to the method described in our recently published article [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…(Yao et al, 2022) XIST is a potential diagnostic marker of triple-negative breast cancer, colorectal cancer, and acute myocardial infarction, and 53BP1 combined with XIST is a prognostic marker of BRCA1-like breast cancer. (Lan et al, 2021;Schouten et al, 2016;Yu et al, 2020a;Zheng et al, 2022) XIST plays a proinflammatory role in epilepsy and neuropathic pain by acting as a ceRNA of miRNA. Zhang et al observed the expression of XIST and NFAT5 in CTX-TNA2 astrocyte cell line treated by LPS was significantly increased, while the expression of miR-29c-3p was decreased.…”
Section: Downloaded Frommentioning
confidence: 99%